Indigenous Knowledge Pertaining to Health, Illness and Healthcare Seeking Behaviour Among Tribes of Chhattisgarh, India: A Comparative Explanation - Dhanjal, Harshdeep Singh; K.K.N, Sharma (Asian Journal of Interdisciplinary Research, 2022)
Tribal population in India constitutes about 8.6 percent of the country’s total population and there are 705 recognized scheduled tribes in the country out of which 75 are declared Particularly Vulnerable Tribal Groups (PVTGs). Tribals reside in the hilly terrains, dense forests in the remote areas perched away from the mainstream depending upon the forests for their routine needs. The interaction of tribal people with nature is intertwined with their indigenous knowledge system, the knowledge which is held by the members of a particular community and evolved through many years of regular experimentation. It is handed down through generations by the mode of cultural transmission. The characteristic feature of indigenous knowledge is that it serves the day to day needs of the tribals and some crises situation of life including health. Health is an inevitable prerequisite is influenced by some common beliefs, practices and customs in any society. Like every culture, tribals as well have their own beliefs and practices with respect to the concept of health, disease and illness. The present study is conducted among tribes of Surguja district of Chhattisgarh and lays emphasis on highlighting the perceptions pertaining to health & illness and beliefs associated with their indigenous knowledge system.